Effectiveness of a dietary re-education and physical activity program on obesity - Heloá Costa Borim Christinelli; Jean Marcel Schmitz de Souza; Maria Antonia Ramos Costa; Élen Ferraz Teston; Maria Luiza Costa Borim; Carlos Alexandre Molena Fernandes (Universidade Federal do Rio Grande do Sul, 2020)
ABSTRACT Objective: To evaluate the effects on obesity of a weight loss method that associates dietary re-education and physical activity. Method: A retrospective, cross-sectional, and quantitative study using secondary data from individual follow-up forms of a weight loss clinic located in a municipality in northwestern Paraná, Brazil. Data collection took place in August 2018 through a checklist of anthropometric parameters, being stored in Excel spreadsheets and analyzed by descriptive statistics using the SPSS program. Results: The mean weight loss was 15.22 kg, and the weight loss method was associated with beneficial results in relation to the following variables: weight, body mass index, body and visceral fat, muscle mass, basal metabolism rate, waist circumference, and hip circumference. Conclusion: The association of dietary re-education with regular physical exercise has a positive impact on obesity.